2012
DOI: 10.1021/nl203060j
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Thermal Conductance at Metal–Graphene Contacts via Chemical Functionalization

Abstract: Graphene-based devices have garnered tremendous attention due to the unique physical properties arising from this purely two-dimensional carbon sheet leading to tremendous efficiency in the transport of thermal carriers (i.e., phonons). However, it is necessary for this two-dimensional material to be able to efficiently transport heat into the surrounding 3D device architecture in order to fully capitalize on its intrinsic transport capabilities. Therefore, the thermal boundary conductance at graphene interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
216
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 247 publications
(235 citation statements)
references
References 44 publications
19
216
0
Order By: Relevance
“…A similar trend has been reported on the Al/graphene interface 33 . H has been shown to diminish the adhesion force between diamond and aluminum 30 .…”
Section: Introductionsupporting
confidence: 87%
“…A similar trend has been reported on the Al/graphene interface 33 . H has been shown to diminish the adhesion force between diamond and aluminum 30 .…”
Section: Introductionsupporting
confidence: 87%
“…Collins et al 9 found that oxygenation and hydrogenation of diamond change the TBC between Al and diamond, to higher values for the former and lower for the latter. Finally, Hopkins et al 10 recently reproduced this result with graphene instead of diamond and observed the same trends as Collins et al. In this paper, we extend the work by Collins et al 9 and we present a thorough investigation of the effect of various surface treatments on the Al/diamond TBC.…”
Section: Introductionsupporting
confidence: 84%
“…Therefore, the interfacial zones predominantly affect the thermal conductivity of the composite [245,246]. As a result, anything that can affect the interfacial regions (e.g., geometry of particles [247][248][249][250][251][252][253], aggregation [254][255][256], interfacial pressure [257], roughness [258][259][260], and the strength of interactions at the interfaces [261][262][263][264][265]) in the composites would influence their thermal conductivity. In this section, we will review the parameters affecting the interfacial interactions and their subsequent impact on the thermal conductivity of the composites.…”
Section: Thermal Conductivitymentioning
confidence: 99%